2012
DOI: 10.1158/1940-6207.capr-11-0441
|View full text |Cite
|
Sign up to set email alerts
|

The State of Molecular Biomarkers for the Early Detection of Lung Cancer

Abstract: Using biomarkers to select the most at-risk population, to detect the disease while measurable and yet not clinically apparent has been the goal of many investigations. Recent advances in molecular strategies and analytic platforms, including genomics, epigenomics, proteomics, and metabolomics, have identified increasing numbers of potential biomarkers in the blood, urine, exhaled breath condensate, bronchial specimens, saliva, and sputum, but none have yet moved to the clinical setting. Therefore, there is a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(151 citation statements)
references
References 120 publications
2
148
0
1
Order By: Relevance
“…[36][37][38] Hassanein et al reported that the abnormal proliferation of cancer cells is the fundamental principle underlying the component analysis of metabolites in cancer patients; in particular, these researchers propose that cancer cell proliferation may lead to abnormal protein expression, thereby causing the peroxidation of cell membranes and the release of VOCs. 39 In blood samples from CRC patients, we detected VOCs, such as 1,1,4,4-tetramethyl-2,5-dimethylene-cyclohexane, that were consistent with the CRC-specific VOCs that Altomare reported in 2013. One of the metabolites detected by Altomare was cyclohexane, which has the same fundamental chemical structure as the 1,1,4,4-tetramethyl-2,5-dimethylene-cyclohexane that was identified in our study but differs only with respect to substituents.…”
Section: Discussionsupporting
confidence: 86%
“…[36][37][38] Hassanein et al reported that the abnormal proliferation of cancer cells is the fundamental principle underlying the component analysis of metabolites in cancer patients; in particular, these researchers propose that cancer cell proliferation may lead to abnormal protein expression, thereby causing the peroxidation of cell membranes and the release of VOCs. 39 In blood samples from CRC patients, we detected VOCs, such as 1,1,4,4-tetramethyl-2,5-dimethylene-cyclohexane, that were consistent with the CRC-specific VOCs that Altomare reported in 2013. One of the metabolites detected by Altomare was cyclohexane, which has the same fundamental chemical structure as the 1,1,4,4-tetramethyl-2,5-dimethylene-cyclohexane that was identified in our study but differs only with respect to substituents.…”
Section: Discussionsupporting
confidence: 86%
“…There is thus a pressing need for a new biofluid-based screening test that can identify high-risk individuals who can then be investigated using more invasive tissue biopsy methodology (Hassanein et al 2012). The crucial role of lipids in cell, tissue and organ physiology is demonstrated by a large number of genetic studies and by many human diseases that involve the disruption of lipid metabolic enzymes and pathways (Wenk, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Möglicherweise kann aber durch den Einschluss genetischer oder molekularer Biomarker eine Verbesserung der Risikomodelle erreicht werden. Derzeit ist jedoch noch keiner dieser Biomarker oder Risikogene zur klinischen Anwendung geeignet [10]. Experimentelle Ansätze konnten zeigen, dass Genanalysen des Nasalepithels von Rauchern als Surrogatparameter dienen könnten, um den schadhaften Effekt des Rauchens auf die Lunge zu beurteilen [30].…”
Section: Bach/spitzunclassified